Study of some parameters of vegetative growth and stomata in wheat by the effect of Nano silica and levels of salt stress - AL-Hassnawi , Fatima Al-Zahra Mahdi; Al-Burki, Fouad Razzaq (Journal of Kerbala for Agricultural Sciences, 2022)
A field experiment was conducted at the second agricultural experiment station of College of Agriculture- Al-Muthanna University during the agricultural season 2021-2022 to study some physiological and phenotypic parameters of three cultivars of bread wheat (Furat, Mawaddah, and Russi) by the effect of foliar apply of Nano silica (100 ppm) and irrigation with three levels of salinity (2.5, 5, 10 ds m-1). The experiment was carried out using the split-split plot design with three replications, the salinity factor (S) was included in the main plot, the Nano silica (N) was included in the secondary plot, and the sub-secondary plot were for cultivars (V). The results of statistical analysis showed that some traits recorded a significant decrease, such as flag leaf area, which decreased by 22.5%, root length, decreased by 16.83%, and the dry weight, by 19.2%, due to the influence of salinity. The results indicated that although Nano silica had a positive effect on root length, which increased by 10.89%, but it had a negative effect on stomata width on the lower surface of leaves, which decreased by (8.75%). The Furat cultivar is superior to the other cultivars in terms of root length, dry weight, stomata width in the upper surface and stomata length in the lower surface.